Cost-effectiveness of valsartan+sakubitril, dapagliflosin and empagliflosin for prevention of cardiovascular death and reducing cardiovascular mortality within the State Program "Health Development" in patients with heart failure - M. V. Zhuravleva; S. N. Tereshchenko; F. N. Paleev; Yu. V. Gagarina; E. A. Shabalina (Российский кардиологический журнал)
Aim. To assess cost-effectiveness of valsartan+sakubitril, dapagliflosin and empagliflosin for prevention of cardiovascular death and achieving the target indicator "reduction of cardiovascular mortality" of the State Program "Health Development" in patients with heart failure (HF) of the entire profile of left ventricular ejection fraction in 2023-2024Material and methods. The target population was Russian patients who had acute cardiovascular disease (CVD) and a verified diagnosis of HF and received subsidized drug coverage. Parametric modeling was used to predict cardiovascular mortality. In the corresponding comparative pair, the amount of drug costs required to prevent one cardiovascular death (CVD) was calculated, as well as to achieve a 1% target for reducing cardiovascular mortality in the whole country and separately in each region.Results. To prevent one cardiovascular event, the costs of 1-year val-sartan+sacubitril therapy was RUB11,80 million, dapagliflozin — RUB7,07 million, empagliflozin — RUB13,83 million. The costs required to achieve a 1% target for reducing cardiovascular mortality for valsartan+sacubitril, dapagliflozin and empagliflozin were:• in 2023, RUB6534,0 million, RUB3915,0 million and RUB7654,2 million, respectively;• in 2024, RUB1100,6 million, RUB659,5 million and RUB1289,7 million, respectively.Conclusion. The use of dapagliflozin is characterized by the lowest costs for preventing one cardiovascular event and achieving a 1% target for reducing cardiovascular mortality in 2023-2024.